Based on the Non-Place Theory, Observations of Individual Behaviour and Private Identity in Non-Place - Liu, Boyu (International Journal of Social Sciences and Public Administration, 2025)
Based on the development of a hypermodern society, social public places and places of transport form spaces of memory, as well as fixed social boundaries consisting of non-places with temporary tenses. By describing and analyzing non-places, the communicative properties that people have in places and for the establishment of personal emotions are demonstrated in reverse. ‘Over the years, these technological systems have become essential to our daily lives, but they are often hidden behind walls or underground and relegated to the realm of the subconscious. It's hard to admit our almost total dependence on them.’ -Nancy Holt. In modern society, the non-place is the connection between two ‘places’, forming an independent and lonely space between them, but the existence of this space is not a passive moment, but rather a space of preparation and accumulation of emotions, which enables people in this space to enter the next ‘place’ in a better way. ‘place’. This spatial typology is born out of a situation of hypermodernity, defined by the acceleration of history, the proliferation of events, and the excess of space. It exists but does not act as a refuge for any organic society.